Idade e crescimento da pessoa-do-Piauí, Plagioscion squamosissimus (Heckel) (Osteichthyes, Sciaenidae), do Açude Amanari (Maranguape, Ceará) - Nomura, Hitoshi; de Oliveira Chacon, João (Revista Ceres, 2025)
Scales and otoliths of Plagioscion squamosissimus (Heckel), a Sciaenidae fish occurring at Amanari Reservoir, in Northeastern Brazil, were collected for the determination of age and growth.